2005
DOI: 10.1128/aac.49.10.4035-4041.2005
|View full text |Cite
|
Sign up to set email alerts
|

Novel, Single-Dose Microsphere Formulation of Azithromycin versus 7-Day Levofloxacin Therapy for Treatment of Mild to Moderate Community-Acquired Pneumonia in Adults

Abstract: This randomized, double-blind, noninferiority study was designed to demonstrate that a single 2.0-g oral dose of a novel microsphere formulation of azithromycin was at least as effective as 7 days of levofloxacin, 500 mg/day, in the treatment of adult patients with mild to moderate community-acquired pneumonia (Fine classes I, II, and III). In total, 427 subjects were randomly assigned to receive either a single 2.0-g dose of azithromycin microspheres (n ‫؍‬ 213) or a 7-day regimen of levofloxacin (n ‫؍‬ 214).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 26 publications
1
42
0
6
Order By: Relevance
“…14,15,[19][20][21][26][27][28][31][32][33][34][35][36] Overall, treatment with fluoroquinolones was successful for 84.2% of patients. Treatment with comparator antibiotics was successful for 82.2% of patients.…”
Section: Treatment Successmentioning
confidence: 99%
See 3 more Smart Citations
“…14,15,[19][20][21][26][27][28][31][32][33][34][35][36] Overall, treatment with fluoroquinolones was successful for 84.2% of patients. Treatment with comparator antibiotics was successful for 82.2% of patients.…”
Section: Treatment Successmentioning
confidence: 99%
“…Data about mortality in the intention-to-treat population were provided in 18 trials [14][15][16][17][18][19]21,22,24,26,27,[29][30][31][32][33][34]36 and ranged from 0% to 7% (mean 2.7%) in the fluoroquinolone groups and from 0.5% to 8% (mean 3.4%) in the comparator groups. Mortality rates were not different between the 2 groups of patients (Figure 2, OR 0.85, 95% CI 0.65-1.12).…”
Section: Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Those results indicated that a single 2-g dose of oral azithromycin leads to higher concentrations in both serum and alveolar macrophages, the same as intravenous azithromycin, although the AUC0-24 in alveolar macrophages from a single 2-g dose of oral azithromycin was approximately half of that with intravenous administration, and the measured concentrations differed between subjects. Single 2-g doses of oral azithromycin are reportedly well tolerated and as effective as a 7-day course of levofloxacin in the treatment of mild to moderate CAP among adult outpatients (10). Although Legionella pneumonia was not evaluated in this study, a single 2-g dose of azithromycin could represent a useful treatment option for mild to moderate Legionella pneumonia as well as other pneumonias, because of the high concentrations indicated above.…”
mentioning
confidence: 96%